Soil mycoflora of Thi-Qar marshes and their enzymatic activities - Al-Duboon, A.H.A.; Mashhad, M.H. (Mesopotamian Journal of Marine Sciences, 2022)
A survey on soil mycoflora in Thi-Qar marshes have been studied. A total of 22 fungal species belonging to 13 genera were isolated and identified. The average of the total fungal colony count ranged between 1550-4150 colonies/gm of soil. Aspergillus, Alternaria, Cladosporium, Stachybotrys and Phoma were of the mostly occurred genera in soil samples constituting 98.67%, 82.67%, 69.33%, 57.0% and 52.0%, respectively, and the mostly occurred species were; A. terreus, A. flavus, C. cladosporioides and S. atra; constituting 74.67%, 69.33%, 69.33% and 57%, respectively. Nine fungal species: Alternaria chlamydospora, Aspergillus flavus, A. fumigatus, A. terreus, Bipolaris spicifera, Fusarium oxysporum, Exserohilum rostratum, Trichoderma viride and Ulocladium botrytis were identified to produce the four investigated enzymes: cellulase, amylase, lipase and protease. All the tested isolates were identified as cellulase and amylase producers, A. candidus, A. flavus, B. spicifera and C. cladosporioides were an excellent producer of cellulase, while A. terreus, Stachybotrys atra and T. viride were the most active amylase producers. A. flavus, F. oxysporum and U. atrum showed the highest lipase production. The higher activity of protease was produced by A. candidus, A. flavus and T. viride.